Sportivnaya aktivnost' zhenshchin Pol'shi - Drozdovsky, Z.; Kelbasevitch-Drozdovska, I. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The aim of this study was to analyze the main aspects of Polish women's activities in the area of sports for all. The next problems were the objects for the analysis: the sporting activities of Poles in various age periods; the reasons of physical activities' shortage; favourable types of sport in various age groups of females; poles' sporting activities in the aspect of the women's sport. Questionnairing of 10 000 persons from 4 regions of Poland served as a material for this study. The obtained data allowed to state that the decreasing physical and sporting activities of women in ontogenesis influences directly on sporting activities of future generations. The patterns of sporting behaviour accepted in a family are not very optimistic. The authors show the various character of sporting activities in the demographycal groups of women's population in Poland.